One Facet of Ethnic Categorization, Ethnicization and Ethnic Activism in Nepal - Acharya, Pradeep (Dhaulagiri Journal of Sociology and Anthropology, 2021)
Ethnicity and identity. particularly for Nepal with diverse human and cultural groups, has become more important in the context of number of ethnic upsurges accompanying macro-level social movements in Nepal, resulting in a radical transformation in the political system. Given the context, this paper aimed to reflect one of the many dimensions of ethnic activism in historical context focused on one of Nepal’s least studied ethnic groups, the Paharis. Further, the paper also attempted to connect the categorization of human groups with the politics of identity. The paper is prepared by extensive reviews supplemented by a number of in-depth interviews among the given community around Kathmandu, Lalitpur, Kabhrepalanchok, and Sindhupalchok district. The paper concludes that Pahari ethnicity and activism have their own trajectory within the broader ethnic movement and activism that became apparent after 1990, followed by the movement initiated by other ethnic groups.